Integer Programming and Combinatorial Optimization 24th International Conference, IPCO 2023, Madison, WI, USA, June 21-23, 2023, Proceedings - Del Pia, Alberto; Kaibel, Volker (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 24th International Conference on Integer Programming and Combinatorial Optimization, IPCO 2023, held in Madison, WI, USA, during June 21-23, 2023. The 33 full papers presented were carefully reviewed and selected from 119 submissions. IPCO is under the auspices of the Mathematical Optimization Society, and it is an important forum for presenting present recent developments in theory, computation, and applications. The scope of IPCO is viewed in a broad sense, to include algorithmic and structural results in integer programming and combinatorial optimization as well as revealing computational studies and novel applications of discrete optimization to practical problems.
Keywords: Computer science -- Mathematics; Mathematics -- Data processing; Discrete mathematics; Application software; Mathematics of Computing; Computational Mathematics and Numerical Analysis; Discrete Mathematics in Computer Science; Computer and Information Systems Applications